KATA SIFAT DALAM NOVELA ANIMAL FARM OLEH GEORGE ORWELL - Mintalangi, Kevin; Pamantung, Rina P.; Manus, Jeane A. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACTÂ Â Â Â Â Â Â Â Â Â The research is entitled â€œKata Sifat Dalam Novella Animal Farm Oleh George Orwell â€. The objectives of this research are to identify and classify types of adjectives in the novella Animal Farm by George Orwell (1945). It is also to analyze and describe the functions of adjective in the novella. This research uses a descriptive method andÂ the theory by Collins andÂ Hollo (2000). The results show there are 122 adjectives in which 76 of them are the gradable type of adjectives and 46 are non-gradable types of adjectives. The gradable types of adjectives are further devided into absolute adjectives (46 words), comparative adjectives (8 words) and superlative adjectives (2 words). There are two functions of adjectives in the novella. The first one is attributive function (114 words)Â and the second one is predicative function (8 words).___________________________Â Â Â Â Â Â Â Â Keywords: Adjectives, Types, Functions, Gradable, Non-Gradable